Youth created media on the climate crisis hear our voices - Beach, Richard ca. 20./21. Jhr; Smith, Blaine E. (Routledge, Taylor & Francis Group, 2024)
This timely book provides effective methods and authentic examples of teaching about climate change through digital and multimodal media production in the English Language Arts classroom. The chapters in this edited volume demonstrate the benefits of addressing climate change in the classroom through innovative media production and cover a range of different types of media, including video/digital storytelling, social media, art, music, and writing, with rich resources for instruction in every chapter.Through the engaging ideas and strategies, the contributors equip educators with the critical tools for supporting students’ media production. In so doing, they offer new perspectives on how students can employ media and production techniques to critique the status quo, call for change, and acquire new literacy skills. As the effects of the climate crisis become increasingly visible to the youth population, this book helps foster and support youth agency and activism. Youth Media Creation on the Climate Change Crisis: Hear Our Voices is a necessary text for students, preservice teachers, and educators in literacy education, media studies, social and environmental studies, and STEM education.The eBook+ version of the text features embedded audio and video components as well as interactive links to reflect the multimodal nature of students’ work, spotlighting how youth media production supports the development of students’ critical literacy skills and shapes their voices and identities